The Fear of Missing Out (FoMO) Phenomenon in the Use of Instagram in Communication Science Students of UIN North Sumatra - Nurhayati, Sri; Azhar, Anang Anas (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
The use of social media, especially Instagram media, has experienced an increase in users without exception, students also participate as Instagram users with a variety of content. However, it is a phenomenon for every user with a record of being tied to Instagram media experiencing FoMO, meaning they feel worried when they miss information or worry when they don't know about activities circulating on social media, especially Instagram media. The influence of this anxiety has an impact on the behavior and attitudes of every social media user. Feelings of FoMO can be reduced by focusing on yourself, limiting excessive use of Instagram and gadgets, seeking real connections, and respecting yourself. This study aims to find out how fear of missing out (FoMO) is for Instagram users in communication science students at UIN North Sumatra. This study uses a descriptive qualitative method with data collection methods through observation and interviews. Informants in this study amounted to 6 people. Alfared Schutz's phenomonological theory which unites scientific knowledge with life experiences and daily activities that are used as experiences. The results of the study show that FoMO occurs in Instagram users due to following trends, recommendations from friends, to fill spare time, looking for information (stalking), business and others. FoMO can be caused by two factors, namely social factors, influenced because they are afraid of being left behind by a trend and are not connected to the conversations of their friends or other people. Personal factors are influenced for fear of being left behind by existing trends, using Instagram for a long time to get satisfaction for himself. This is what can cause FoMO symptoms by someone where the person feels dependent on Instagram, checks Instagram all the time and feels anxious if they cannot access or are not connected to Instagram.